DNA aptamers for the recognition of HMGB1 from Plasmodium falciparum - Joseph, Diego F. (2019)
Rapid Diagnostic Tests (RDTs) for malaria are restricted to a few biomarkers and antibody-mediated detection. However, the expression of commonly used biomarkers varies geographically and the sensibility of immunodetection can be affected by batch-to-batch differences or limited thermal stability. In this study we aimed to overcome these limitations by identifying a potential biomarker and by developing molecular sensors based on aptamer technology. Using gene expression databases, ribosome profiling analysis, and structural modeling, we find that the High Mobility Group Box 1 protein (HMGB1) of Plasmodium falciparum is highly expressed, structurally stable, and present along all blood-stages of P. falciparum infection. To develop biosensors, we used in vitro evolution techniques to produce DNA aptamers for the recombinantly expressed HMG-box, the conserved domain of HMGB1. An evolutionary approach for evaluating the dynamics of aptamer populations suggested three predominant aptamer motifs. Representatives of the aptamer families were tested for binding parameters to the HMG-box domain using microscale thermophoresis and rapid kinetics. Dissociation constants of the aptamers varied over two orders of magnitude between nano- and micromolar ranges while the aptamer-HMG-box interaction occurred in a few seconds. The specificity of aptamer binding to the HMG-box of P. falciparum compared to its human homolog depended on pH conditions. Altogether, our study proposes HMGB1 as a candidate biomarker and a set of sensing aptamers that can be further developed into rapid diagnostic tests for P. falciparum detection.